The effects of storage of red blood cells on the development of postoperative infections after noncardiac surgery. Issue 11 (7th August 2017) - Spadaro, Savino; Taccone, Fabio Silvio; Fogagnolo, Alberto; Fontana, Vito; Ragazzi, Riccardo; Verri, Marco; Valpiani, Giorgia; Greco, Pantaleo; Bianconi, Margherita; Govoni, Maurizio; Reverberi, Roberto; Volta, Carlo Alberto
Abstract : BACKGROUND: Prolonged storage of red blood cells (RBCs) is a potential risk factor for postoperative infections. The objective of this study was to examine the effect of age of RBCs transfused on development of postoperative infection. STUDY DESIGN AND METHODS: In this prospective, double‐blind randomized trial, 199 patients undergoing elective noncardiac surgery and requiring RBC transfusion were assigned to receive nonleukoreduced RBCs stored for not more than 14 days ("fresh blood" group, n = 101) or for more than 14 days ("old blood" group, n = 98). The primary outcome was occurrence of infection within 28 days after surgery; secondary outcomes were postoperative acute kidney injury (AKI), in‐hospital and 90‐day mortality, admission to intensive care unit, and hospital length of stay (LOS). As older blood was not always available, an "as‐treated" (AT) analysis was also performed according to actual age of the RBCs transfused. RESULTS: The median [interquartile range] storage time of RBCs was 6 [5‐10] and 15 [11‐20] days in fresh blood and in old blood groups, respectively. The occurrence of postoperative infection did not differ between groups (fresh blood 22% vs. old blood 25%; relative risk [RR], 1.17; confidence interval [CI], 0.71‐1.93), although wound infections occurred more frequently in old blood (15% vs. 5%; RR, 3.09; CI, 1.17‐ 8.18). Patients receiving older units had a higher rate of AKI (24% vs. 6%; p < 0.001) and, according to AT analysis, longer LOS (mean difference, 3.6 days; CI, 0.6‐7.5). CONCLUSION: Prolonged RBC storage time did not increase the risk of postoperative infection. However, old blood transfusion increased wound infections rate and incidence of AKI.